Long-term clinical course of adult-onset refractory epilepsy in cardiofaciocutaneous syndrome with a pathogenic MAP2K1 variant: a case report - Tsuburaya-Suzuki, Rie; Ohori, Sachiko; Hamanaka, Kohei; Fujita, Atsushi; Matsumoto, Naomichi; Kinoshita, Masako (Frontiers in Genetics, 2024)
Cardiofaciocutaneous syndrome (CFC) is a rare genetic disorder that presents with cardiac, craniofacial, and cutaneous symptoms, and is often accompanied by neurological abnormalities, including neurodevelopmental disorders and epilepsy. Regarding epilepsy in CFC, the onset of seizures commonly occurs in childhood. Since research data has mainly been collected from young patients with relatively short observation period, there is insufficient information regarding adult-onset epilepsy in CFC. Here, we report the long-term clinical course of epilepsy and other complications in a 45-year-old female with genetically confirmed CFC carrying a pathogenic de novo heterozygous variant of MAP2K1, c.389 A>G (p.Tyr130Cys). The patient presented psychomotor delay from infancy and had severe intellectual disability with autistic features. At the age of 30, she first developed combined generalized and focal epilepsy that was resistant to anti-seizure medication. Her refractory epilepsy was fairly controlled with a combination of three anti-seizure medications, especially lacosamide, which effectively suppressed both generalized and focal seizures. The present case provides detailed information regarding the clinical course and treatment of adult-onset epilepsy, which may be useful for optimal treatment and prognostic prediction of CFC.